Sexual Differentiation of the Brain in Man and Animals: Of Relevance to Klinefelter Syndrome? - McCarthy, MARGARET M. (Am J Med Genet C Semin Med Genet, 2013)
The developing brain is highly sensitive to the organizing effects of steroids of gonadal origin in a process referred to as sexual differentiation. Early hormone effects prime the brain for adult sensitivity to the appropriate hormonal milieu, maximizing reproductive fitness via coordinated physiology and behavior. Animal models, in particular rodents, have provided insight into general principles and the cellular and molecular mechanisms of brain differentiation. Cellular endpoints influenced by steroids in the developing brain include neurogenesis, migration, apoptosis, dendritic growth, and synaptic patterning. Important roles for prostaglandins, endocanabinoids, and epigenetics are among the many cellular mediators of hormonal organization. Transference of general principles of brain sexual differentiation to humans relies on observations of individuals with genetic anomalies that either increase or decrease hormone exposure and sensitivity. The physiology and behavior of individuals with XXY (Klinefelter syndrome) has not been considered in the context of sexual differentiation of the brain, most likely due to the delay in diagnoses and highly variable presentation. The behavioral phenotype and impairments in the domains of speech and language that are characteristic of individuals with XXY is consistent with the reduced androgen production associated with the syndrome. Hormone replacement appears effective in restoring some deficits and impact may be further improved by increased understanding of the hormonally mediated sexual differentiation of the brain.